Medical management of a case of central giant cell granuloma masquerading as a periapical pathosis - Balaji Babu Bangi; Lakshmi Kavitha Nadendla; Revath Vyas Devulapalli; Archana Pokala (Wolters Kluwer Medknow Publications, 2015)
Lesions of non-endodontic origin may mimic periapical pathosis. Errors in one or more of the clinical reasoning steps of diagnosis of such lesions may ultimately lead to misdiagnosis and ensuing complications. Central giant cell granuloma (CGCG) is one such lesion of non-endodontic origin which can present as periapical pathosis. Here, we present a case of CGCG in a 33-year-old female patient who visited our department with a complaint of growth from the extraction sockets of upper front teeth, which were extracted 1 month back after a misdiagnosis as periapical pathosis. Suspecting a non-endodontic lesion, radiographic examination and incisional biopsy were performed and a final diagnosis of CGCG was made. Biweekly intra-lesional steroids were given for 6 weeks and patient was followed up for 6 months.